2018
DOI: 10.1007/s00586-018-5746-2
|View full text |Cite
|
Sign up to set email alerts
|

Observational retrospective study on socio-economic and quality of life outcomes in 41 patients with adolescent idiopathic scoliosis 5 years after bracing combined with physiotherapeutic scoliosis-specific exercises (PSSE)

Abstract: Compared with the literature, our results showed similar curve development and hrQoL (pain, self-image and function) and better results regarding satisfaction with treatment. In comparison with the average population, there were no disadvantages as to occupation, education and sports. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Others reported that wearing a brace may lead to various psychological reactions such as negative thoughts, stress and anxiety, emotional instability, and disturbance of self-image or self-esteem of individuals with AIS [9][10][11] . These differences might be due to the level of satisfaction with management 12) , severity of scoliosis curvature 13) , brace type 14) , cultural differences, and brace-related stress 15,16) . In some societies, individuals use a special cover when they appear in the society to hide the brace underneath the dress and therefore reduce the psychological effect of the brace 9,10) .…”
Section: Introductionmentioning
confidence: 99%
“…Others reported that wearing a brace may lead to various psychological reactions such as negative thoughts, stress and anxiety, emotional instability, and disturbance of self-image or self-esteem of individuals with AIS [9][10][11] . These differences might be due to the level of satisfaction with management 12) , severity of scoliosis curvature 13) , brace type 14) , cultural differences, and brace-related stress 15,16) . In some societies, individuals use a special cover when they appear in the society to hide the brace underneath the dress and therefore reduce the psychological effect of the brace 9,10) .…”
Section: Introductionmentioning
confidence: 99%